Making Islamic popular music in Malaysia, 1996-2016 - Mohamad Haris, Mohamad Fitri (2019)
The purpose of this research is to analyse the development of the nasyid genre in the Malaysian music industry over a period of two decades (1996-2016), from the perspectives of the producers of this music. The word nasyid derives from Arabic, which means ‘to sing or chant’. The research seeks to provide further understanding of nasyid and to consider various perspectives on the changes that took place over the period under scrutiny. The research addresses the so-called ‘Raihan phenomenon’ of the late 1990s, which led to a growth in nasyid as a genre of Islamic popular music. The thesis explores both the genre of nasyid and its wider landscape and context. It also investigates the changes regarding musical instruments and musical style, analyses the lyrics and languages of the music and the evolution of images and the changing retinue of the participants in this musical genre. Furthermore, this research considers the scope and structure of the music business and the marketing practices that surrounded nasyid in Malaysia. As an insider to, and a veteran of, the Muslim Malay music industry, the author uses his knowledge and insights to enhance understanding of nasyid in Malaysia. The study uses qualitative research techniques including multiple analysis methods, in-depth interviews, content analysis and participant-observation fieldwork. This fieldwork was carried out in two phases, over 11 months (September 2015 to January 2016 and April 2016 to September 2016), with industry experts, singers, composers, lyricists, arrangers and musicians, Islamic scholars, media workers, and music retailers, as well as related organisations and recording labels working in the Malaysian music industry, especially within the genre of nasyid. The findings and results of this study show how nasyid grew rapidly over the two decades in question. The research draws together knowledge from respondents experienced in the Malaysian music industry; a key aim is to use this knowledge to enhance the commercial viability of nasyid in the Malaysian music industry and beyond. The conclusion summarises three major findings, namely: (i) the complexity of defining Islamic popular music and nasyid; (ii) the style and characteristics of nasyid and Islamic popular music in Malaysia; and (iii) the place of halal literacy within the business models used by the music industry of Malaysia. Suitable recommendations are put forward to help maintain this music in the future by considering the training systems for educating emerging nasyid artists. Overall, this thesis seeks to achieve three things, namely: (i) provide detailed knowledge on this music for international scholars of ethnomusicology and popular music studies; (ii) inform participants in nasyid and related Islamic music genres about the structure of the industry; and (iii) present ideas on the business models deployed and provide suggestions for improved economic outcomes.